A PRELIMINARY STUDY OF DIVERSITY OF BUTTERFLIES AROUND GOVIND SAGAR LAKE IN DISTRICT UNA, HIMACHAL PRADESH - SHARMA, KANIKA; KUMARI, VANDANA; LAKHANPAL, DINESH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Papilionoidea is a diverse insect group having economic, cultural and aesthetic values. Himachal Pradesh have varied climatic conditions ranging from tropical in Shivalik foothills to the arctic in the Trans-Himalayan region. These conditions are conducive for diversity of butterflies which further are good indicators of environment health. This preliminary study was conducted to explore butterfly fauna around Govind Sagar Lake in district Una, Himachal Pradesh from 2017-2018. A total of 25 butterfly species belonging to 17 genera and 5 families of order Lepidoptera namely Nymphalidae, Pieridae, Papilionidae, Lycaenidae and Hesperiidae were collected. Nymphalidae represented by 11 species was found to be most dominant followed by Pieridae (9 species), Papilionidae (3 species), Lycaenidae (1 species) and Hesperiidae (1 species). Representative percentage composition of these 5 families showed Nymphalidae constituting around (44%) of total butterfly fauna, followed by Pieridae (36%), Papilionidae (12%), Lycaenidae (4%) and Hesperiidae (4%). This is the first investigation to study the butterfly diversity, distribution and abundance from habitats around the lake in district Una.